HAK UPAH PEKERJA AKIBAT PEMUTUSAN HUBUNGAN KERJA SEPIHAK PERSPEKTIF UNDANG-UNDANG NO. 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (STUDI KASUS: PUTUSAN NOMOR 162/PDT. SUS-PHI.PLW/2019/PN.JKT.PST) - Aufan Ahdi; Gunardi Lie (Fakultas Hukum Universitas Tarumanagara, 2022)
Workers are people who work as well as people who receive wages or work results. Workers andemployers who enter into an employment relationship are required to include a work agreement. In thisemployment relationship, the employer often terminates the employment relationship unilaterallywithout giving rights to workers, including severance pay, service fees, and compensation forentitlements. The author uses normative legal research methods and uses interview data as supportingdata. The results of this study reveal that Decision Number: 162/Pdt. Sus-Phi.Plw/2019 which washanded down by the Panel of Judges in the case of Industrial Relations Disputes that occurred betweenworkers and employers was not in accordance with Article 155 of Law Number 13 of 2003 concerningManpower which in the event of Termination of Employment, in this case the worker must obtainentitlement in the form of wages during the process, which is for a full 6 months. If there is anindustrial relations dispute between workers and employers, it can be resolved through an industrialrelations court outside or through an industrial relations court.